2002
DOI: 10.1128/jvi.76.1.436-443.2002
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Human Immunodeficiency Virus Type 1 Containing Murine Leukemia Virus Matrix Assembles in Murine Cells

Abstract: Murine cells do not support efficient assembly and release of human immunodeficiency virus type 1 (HIV-1) virions. HIV-1-infected mouse cells that express transfected human cyclin T1 synthesize abundant Gag precursor polyprotein, but inefficiently assemble and release virions. This assembly defect may result from a failure of the Gag polyprotein precursor to target to the cell membrane. Plasma membrane targeting of the precursor is mediated by the amino-terminal region of polyprotein. To compensate for the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 15 publications
(12 reference statements)
1
31
0
Order By: Relevance
“…Previous studies have shown that replacement of the HIV-1 MA domain with that of MLV MA can improve HIV-1 assembly in murine cells (3,18). However, such chimeric viruses are poorly infectious and no manipulation has yet succeeded in improving the yield of infectious HIV-1 virions from murine cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that replacement of the HIV-1 MA domain with that of MLV MA can improve HIV-1 assembly in murine cells (3,18). However, such chimeric viruses are poorly infectious and no manipulation has yet succeeded in improving the yield of infectious HIV-1 virions from murine cells.…”
mentioning
confidence: 99%
“…Gag -membrane interaction, processing, and particle release are enhanced by replacing the HIV-1 matrix (MA) domain with that of murine leukemia virus (MLV) (3,18), and this has been interpreted to suggest that a Pr55…”
mentioning
confidence: 99%
“…The MuLV MA protein does not contain an obvious PIP binding site, and poor solubility has thus far precluded high-resolution structural studies of the myristoylated MuLV MA protein. It is possible, however, to replace HIV MA with MuLV MA with limited effects on viral replication, suggesting a conserved function for this domain among retroviruses (10,42). To determine if this evolutionarily distant retrovirus uses a similar PIP-dependent mechanism for membrane targeting of the Gag polyprotein, we prepared and characterized native and mutant forms of MuLV MA mutants.…”
mentioning
confidence: 99%
“…However, evaluating the immunogenicity of HIV-1 Gag VLPs in mice is complicated by the failure of HIV-1 Gag to efficiently assemble VLPs in murine cells. In this study, the problem was overcome by using an MMLV-HIV-1 chimeric Gag that releases significant amounts of VLPs when expressed in murine cells (13,47). This has permitted an evaluation of the role played by in vivo VLP formation in the immunogenicity of HIV-1 Gag.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously demonstrated that murine cells expressing HIV-1 proviral clones in which the p17 matrix domain from HIV-1 Gag was replaced with the p15 matrix and p12 domains from MMLV were able to support plasma membrane localization of Gag in murine cells and release significant amounts of viral particles (13,47). To explore the immunogenicity of such Gag VLPs in vivo, we generated a high-expression form of this construct by fusing p15 and p12 from MMLV Gag in frame with codonoptimized HIV-1 Gag p24, p2, p7, p1, and p6, creating MHGag (Fig.…”
Section: Mmlv-hiv-1 Gag Releases Particulate Antigen When Expressed Imentioning
confidence: 99%